2 - Algérie : le rapport savoir-pouvoir ou le rêve avorté de la différenciation par le savoir - Hocine Khelfaoui, (Journal of Higher Education in Africa, 2010)
This article analyzes relationship between university and political power in Algeria. It describes the evolution of this relationship since independence in a context where the state controls all economic and social activities. In the aftermath of independence, higher education appears first as the gateway to positions highly distinctive and therefore a challenge sociocultural and political center. The result is a process of autonomy of universities which revealed sociopolitical and economic issues that could jeopardize the terms of the relationship between knowledge and power. Therefore, the university is gradually reduced to the tool of subjection and its agents a simple emanation of power. The article shows how political power has become more dependent on the global and the local university has diverted its mission to implement a scientific approach rooted in the culture and nature in line with local and international science.